Conservação à baixa temperatura e avaliação da viabilidade de grãos de pólen de mamoneira - Cuchiara, Cristina Copstein (2010)
The castor bean (Ricinus communis L.) it is known by the high adaptation capacity to the different climate conditions and soil, characteristics these that it possible be her cultivated commercially in different areas of Brazil. Consequently, researches about conservation and germination of the pollen are indispensable to the programs of genetic improvement. The purpose is to evaluate the viability and conservate grains of castor bean pollen. For the study, were used floral buttons of the cultivars IAC 80, AL Guarany 2002 and Lara. In the first experiment, were selected appropriate parameters of pH (5, 6, 7 and 8), temperature (15, 20, 25 and 30 ºC), sucrose (0; 5; 10 and 20%) and combinations of 4, 8 and 10 mgL-1 boron with sucrose. In the second experiment, the storage of pollen was evaluated of the cultivars IAC 80 and AL Guarany 2002 in four places (liquid nitrogen (-196 ºC); ultrafreezer (-72 ºC); freezer (-18 ºC) and refrigerator (4 ºC)) being analyzed week after week to complete thirty days and in the sixty days. The third experiment was evaluated the effect about the time of defreezing of pollen cultivars IAC 80 and AL Guarany 2002, submitted to the same places and storage periods (15, 30 and 60 days) analyzed of hour after hour to complete six hours and after twenty-four hours. The viability test was constituted preparing ideal culture medium for each experiment, after that it was deposited in excavated plates, where the pollen was distributed on the surface of the medium, the plates were put in humid camera and taken for incubation. In random delineation, were analyzed a hundred pollens per repetitions in a total of four repetitions for the first experiment and six for the others. I In the first experiment was observed that pH values above 6,0 cause decrease in the amount of germinated pollens. The temperature of 20 ºC and 5% and 10% of sucrose were appropriate for the germination. Sucrose and 4 and 8 boron mgL-1 increased the germination, however 10 mgL-1 didn't favor. It was observed in the second experiment that the storage in 4 and -18 ºC is not efficient, the number of germinated pollens falls quickly causing unviability after the fifth week, in -72ºC the pollens of the cultivar IAC 80 stayed viable even the fourth week and the cultivar AL Guarany 2002 presented viability the sixty days and -196 ºC was very efficient even to fifth week. With the third experiment can be verified that for the cultivars IAC 80, to the 15 and 30 days of storage, the temperature of the -72 ºC presented around 50% of germination needing five and six hours of incubation for the defreezing, respectively; for the cultivar AL Guarany 2002, the best result was reached to -196 ºC and the sixty days was occurred the unviability. Therefore, the cultivars answered in a different way the best methodology of evaluation of pollen viability and conservation, however, the one that suggests be species-specific.